(untitled) (Journal of Politics and International Studies, 2022)
Regional integrations have changed the design of the world. Correspondingly, it has transformed the living patterns of the regions. High rate of urbanization is one of the major outcomes of this changing world. Pakistan is also a dupe of this change where rate of urbanization is 2.68% annually and more than 60% of population of Pakistan will move to urban areas till 2050 as per UN’s estimate. On the other hand, CPEC is pouring investment in different cities of Pakistan which will further boost urbanization in the country. Urbanization has decreased the service delivery quality gravely in major cities of Pakistan due to numerous snags of governance and situation will be further shoddier due to CPEC projects which will enhance urban livability in Pakistan. Therefore, sound planning and effective urban governance is required for tackling this serious challenge effectually. This research study has explored challenges of urban governance of Pakistan due to CPEC which is really a game changer for the country. Qualitative research methodology has been adopted for exploring the challenges of urban governance in Pakistan due to CPEC’s projects and accomplishments. The explored challenges will help to devise a framework for improving governance of major cities and towns of Pakistan. The proposed framework in this research study will provide solutions for good urban governance of Pakistan which will lead towards sustainable urbanite and efficient service delivery to general public through innovative modes of governance.